Aspek Penerapan Video Segmentasi Sebagai Sistem Pendeteksi Pelanggaran Lalu Lintas - Christian Desamta S; Indra Yasri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This paper describes analysis of video Segmentation and tracking on highway that is done with using edge detection method. In this paper, method of analysis is using help from software matlab simulink. The proccess of analysis is done by making blocks model for proccessing place of segmentation and tracking. The factor in this study is color conversion, motion detection, background subtraction, blob analysis or making contour and tracking. This analysis is using GUI ( Graphical User Interface) for see the result of video on output from each of block and can see the pixel value on video and can do calculation with using the pattern is usin in this study so the result from analysis calculation and analysis from GUI (Graphical User Interface) is matching.Keyword : Video Segmentation, Video Tracking, Edge Detection, Motion Detection, Matlab, Simulink.